Layanan Pendidikan dan Pendekatan yang Digunakan Bagi Anak Berkebutuhan Khusus di Tingkat Sekolah Dasar - Desty Ningtyas Rambu Bazar; Serly Kurniady; Yeni Putiyanti; Opi Andriani (Institut Nalanda, 2024)
This research aims to analyze the implementation of inclusive education for children with special needs in elementary schools. The research method or approach in this research uses a study approach literature or library research. Data and information collection techniques through studies literature. The results of this study state that the existence and role of special guidance teachers or special education teachers in the implementation of inclusive education is very important and even plays a very important role. In schools there tends to be no special guidance teachers or special education teachers, the existing educational staff still do not understand much about the meaning of inclusive education and the existence of ABK.